Association between hypoxia-inducible factor-1 alpha rs11549465 (1772 C>T) polymorphism and metabolic syndrome - Uzma Zafar; Zaima Ali; Saba Khaliq; Khalid Lone (Journal of the Pakistan Medical Association, 2021)
Objectives: To find the association of single nucleotide polymorphism of hypoxia-inducible factor-1 alpha, rs11549465 (1772 Cytosine > Thymine) with metabolic syndrome, and to compare the anthropometric and biochemical variables in different genotypes of hypoxia-inducible factor-1 alpha. Methods: The cross-sectional comparative study was conducted at the University of Health Sciences, Lahore, Pakistan, from July 2016 to April 2019, and comprised patients of metabolic syndrome selected from the Sheikh Zayed Hospital, Lahore. Healthy controls were also enrolled. Fasting venous sample was taken for the determination of study parameters. The genetic variant of hypoxia-inducible factor-1 alpha was analysed by restriction fragment length polymorphism polymerase chain reaction. Data was analysed using SPSS 22. Results: Out of 400 subjects, 200(50%) each were patients and controls. The frequency of CC genotype of hypoxia-inducible factor-1 alpha Cytosine > Thymine in patients was 166(83%) and in controls 147(73.5%); CT genotype was 34(17%) and 53(26.5%) respectively, while TT genotype was not observed. There was a significant association of the C allele and CC genotype (p=0.03) with the increased risk of metabolic syndrome (p=0.02). On comparison of study variables in the two genotypes, systolic blood pressure, anthropometric and lipid parameters were significantly higher in the wild CC genotype compared to CT in the control group (p<0.05), but there was no significant difference in the patients (p>0.05). Conclusion: Major allele C of hypoxia-inducible factor-1 alpha 1772 Cytosine > Thymine was found to be associated with increased risk of metabolic syndrome. Continuous...